A comparison of the maternal levels of serum proprotein convertase subtilisin/kexin type 9 in pregnant women with the complication of fetal open neural tube defects. (23rd June 2021) - Erol, Seyit Ahmet; Tanacan, Atakan; Firat Oguz, Esra; Anuk, Ali Taner; Goncu Ayhan, Sule; Neselioglu, Salim; Sahin, Dilek
Abstract: It was aimed to evaluate the levels of maternal serum proprotein convertase subtilisin/kexin type 9 (PCSK9) in pregnant women with a fetus diagnosed with open neural tube defects (NTDs). This case‐control study included 38 pregnant women carrying fetuses with open NTDs and 44 age‐matched, pregnant women with no specified risk factors. Comparisons were made of the groups in respect of demographic and clinical data and PCSK9 levels. To examine the performance of PCSK9 levels in the prediction of fetal open NTDs, receiver operating characteristic (ROC) curve analysis was used. In the first and second trimesters, PCSK9 levels were determined to be lower in the NTD group than in the control group ( p = 0.010 and p = 0.015, respectively). In the first trimester, the lower PCSK9 levels in the NTD group were not statistically significant ( p = 0.575). In the second trimester, the ROC curve value with the best balance of sensitivity/specificity for PCSK9 was 71.9 ng/ml (84.6% sensitivity, 51.7% specificity) and in the first and second trimester combined, 74.4 ng/ml (81.6% sensitivity, 45.5% specificity) ( p = 0.015, p = 0.036, respectively). PCSK9 may be involved in the etiopathogenesis of open NTDs at the critical steps of fetal neuronal differentiation. Although it has limitations, PCSK9 may be used as an additional biomarker for the screening of NTDs.